Influence of composting and thermal processing on the survival of microbial pathogens and nutritional status of Nigeria sewage sludge - Kayode Fatunla; Edu Inam; Joseph Essien; Emmanuel Dan; Akanimo Odon; Suil Kang; Kirk T. Semple (International Journal of Recycling of Organic Waste in Agriculture)
Abstract Purpose Sewage sludge samples from a water treatment plant in Nigeria were subjected to an in-vessel composting (using sawdust as a bulking agent) and thermal sludge processing to improve its quality for agricultural applications. Methods Treated samples were analyzed for physicochemical and microbiological properties using standard analytical and aerobic culture protocols. Results Microbiological analysis of the initial fresh mixture (sewage sludge/sawdust) showed that the total heterotrophic bacteria was 1.17 × 106 CFU/g of fresh compost, coliforms 4.7 × 104 CFU/g, Salmonella sp., and Shigella sp. 7.3 × 104 CFU/g, yeasts and moulds 9.0 × 104 CFU/g. These values were significantly (p = 0.05) reduced after 40 days of in-vessel composting to 4.3 × 104 CFU/g for total heterotrophic bacteria, 7.4 × 102 CFU/g for coliforms, while yeasts and moulds, Salmonella and Shigella sp. were not detected in the final compost. The results of the physicochemistry revealed variation in pH, temperature, and nutrients status of treated sludge. Conclusion Salmonella sp., Staphylococcus aureus, and Shigella sp. were eliminated, while a 2-log reduction in coliform counts occurred after 40 days of composting. Composting had a better processing impact by increasing the ash as well as reducing the carbon/nitrogen ratio of treated sludge, while thermal processing improved the sulfate and phosphate components of treated sludge. The treated sludge (biosolids) met the permissible limits of microbiological and nutritional standards recommended by US EPA for land application of sludge and could, therefore, be used as a biofertilizer, soil conditioner and also for land reclamation.